The Role of Sufi Networks in Islamic Political and Economic History - Afi, Badrus Sholeh (An-Nur International Journal of Islamic Thought, 2025)
This paper investigates the multifaceted economic roles and institutional structures of Sufi networks in Islamic societies from medieval to modern times. It examines how Sufi doctrines of poverty and wealth, particularly through the divergent views of al-Ghazālī and Ibn Taymiyyah, shaped a distinctive Islamic economic ethos that intertwined spiritual discipline with ethical material engagement. The study explores the institutionalization of Sufi lodges (khānqāhs and zāwiyas) through waqf endowments, revealing how these centers supported religious transmission, community welfare, and local governance. Sufi lineages such as those in the Safavid and Saʿdī dynasties utilized spiritual charisma and household-based waqf networks to consolidate political authority and social influence. In frontier regions like Bengal and agrarian contexts like Morocco, Sufi institutions catalyzed agricultural development and rural integration, while in urban economies, Sufi guidance permeated trade guilds and artisanal ethics. The study also examines shrine-based pilgrimage economies as enduring engines of spiritual devotion, economic redistribution, and local identity formation, even amid modern state interventions and commodification. By integrating interdisciplinary methodologies from economic anthropology, historical sociology, and religious studies, this research highlights the strategic role of Sufi institutions in negotiating material realities with spiritual commitments. It offers new insights into how Sufi networks cultivated socio-economic resilience, governance structures, and moral economies across diverse Islamic polities and periods.